PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT BELAJAR PKN SISWA KELAS II SD NEGERI 157 PEKANBARU - Ramayulis Ramayulis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
Based on the result of observation and experience in class II SD Negeri 157 Pekanbaru found the symptomespecially on the lesson of Civics which showed the lack of interest of student learning on the subjects of Civicsinclude: Majority of children (48.5%) or 17 students from 33 students less attention to the lesson when theteacher explained in front of the class. Of the 33 students, 17 (48.5%) students were less excited or bored by justlooking at the writing without pictures to explain it. The formulation of the problem in this research is Does theuse of media images can increase the interest of learning Civics students class II SD Negeri 157 Pekanbaru?The purpose of this study is to determine the appropriate action in the use of image media in order to increasethe interest of learning Civics students class II SD Negeri 157 Pekanbaru. This classroom action research wasconducted in the second grade of SD Negeri 157 Pekanbaru. Research subjects are all students of class II SDNegeri 157 Pekanbaru with 33 students consisting of 15 students and 18 female students. Based on the results ofthe research note that in the first cycle after improved in cycle II it turns out students' interest in learningincreased with the use of image media. The increase is seen in cycle II. In the first cycle, students' interest inlearning only reached 97 score with 49,0% interest rate indicator, then increase in cycle II reaching score 155with average indicator 78,3%. From the results of research and discussion as described above explains that withthe use of appropriate media images in grade 2 students on the subjects of civic education in SD Negeri 157Pekanbaru then the student activity becomes more active and in turn the students' learning interest becomesbetter. This information proves that the research hypothesis which reads "The use of media images can increasethe interest of learning Civics students class II SD Negeri 157 Pekanbaru" received ".